(3OjhGf CHj MjGfs - (3eMeO Hf jhSa Hf Ydj Hf jhSa GHf nMnqjGf GdZQfGWj GdCfOdSj GdLjGfj, GdpqfraRj, CKjQ GdOjf, CHh MjGf,J (B745 (3g` s
(3ChdgG (B:s
(3bGajI GdgeRI bGd QMeg Gddg(B: (3CdG CHdZ adGf GdOjf YJHi Ydjg abO JeGOi aj GdLaGA s
(3BNQgG (B:s
(3cd bdH aj MHI bO JhGdi cja dG hCSeg Sei GdhUi Je GdOjhGf GdeHGQc HMeO Gddg hYhfg s
(3GdOjhGf eQJH Ydi MQha GdeYLes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B152 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B130s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B92 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B- (3GdQHGW ecJHI hRGf (B(4) s
Keywords: (3GdCOHs